2005
DOI: 10.1016/j.clinph.2004.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of the visual N1 component of event-related potentials by central and peripheral cueing

Abstract: This study provides a detailed within-subject analysis of the time course of the effects of central and peripheral cueing on N1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…The frontal enhancement in the hemispheric regions signifies the increased attention required for the centrally positioned stimuli. Corresponding with Doallo et al's (2005) findings, it is postulated that this central cueing was validated at an expected target's presentation, evoking the larger response to this imperative. However, as these topographic effects have not been reported previously, it is difficult to relate these findings to previous studies, particularly as a second N1 component was identified.…”
Section: N1mentioning
confidence: 77%
“…The frontal enhancement in the hemispheric regions signifies the increased attention required for the centrally positioned stimuli. Corresponding with Doallo et al's (2005) findings, it is postulated that this central cueing was validated at an expected target's presentation, evoking the larger response to this imperative. However, as these topographic effects have not been reported previously, it is difficult to relate these findings to previous studies, particularly as a second N1 component was identified.…”
Section: N1mentioning
confidence: 77%
“…Similar to previous studies (Mangun and Hillyard, 1991;Hopfinger and Ries, 2005), we found evidence for early sensory processing for validly cued compared with invalidly cued locations (indicated by a larger P1 component on valid trials). However, this difference was largely unaffected by cue predictability (Doallo et al, 2005). This dissociation between higher frequency responses in the gammaband range and the low-frequency responses in ERPs suggest that high-and low-frequency EEG activity reflect different neural mechanisms.…”
mentioning
confidence: 78%
“…Voluntary and involuntary attention effects have seldom been directly compared under equal stimulus conditions within the same ERP study. Studies that attempted this comparison revealed no marked differences in the amplitudes of either P1 or N1 (Doallo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies show that stimuli presented at the cued location (valid trials) are detected and discriminated faster and more accurate than that stimuli appearing at unprecued locations (invalid trials). These attentional effects occur in absence of eye movements (covert orienting of attention) (Jonides 1981;Müller and Rabbitt 1989;Posner 1980;Posner, Nissen and Ogden 1978;Doallo, Lorenzo-Lopez, Vizoso, Holguin, Amenedo, Bara and Cadaveira 2005).…”
Section: Introductionmentioning
confidence: 97%